RELATIONSHIP BETWEEN COMMUNITY KNOWLEDGE AND PARTICIPATION IN CORAL REEF CONSERVATION ON SEBESI ISLAND, INDONESIA - Khadijah; Meisy Legiawati; Amara Choirunisa; Apria Pamilda; Rezhati Rahmalia; Ni Wayan Rintan Malika Putri; Ridwan Ali Sahroni; Reza Raihandi Akbar; M. Rizko Fajrin; David Julian; Muhammad Reza (Jurusan Perikanan dan Kelautan, 2026)
Community participa-tion is a key factor in supporting the sustainability of coral reef ecosystems, particularly in small island communities that rely heavily on marine resources. Community knowledge is considered one of the factors that may influence participation in conservation efforts. This study aimed to analyze the relationship between community knowledge and participation in coral reef ecosystem conservation on Sebesi Island, Lampung Province, Indonesia. A quantitative survey approach was employed using structured questionnaires administered to 30 respondents selected from the local community. The research instrument was tested for validity and reliability prior to data collection. Data were analyzed using descriptive statistics and Pearson correlation analysis at a significance level of 5%. The results indicated that community knowledge regarding coral reef conservation was generally in the good category, as was the level of community participation in conservation activities. Pearson correlation analysis revealed a strong positive relationship between community knowledge and participation (r = 0.690; p < 0.05), indicating that higher levels of knowledge were associated with greater community involvement in coral reef conservation. These findings suggest that improving environmental knowledge through education, outreach, and community empowerment programs may enhance public participation in coral reef ecosystem conservation. The study provides empirical evidence to support community-based conservation strategies for the sustainable management of coral reef ecosystems on small islands.